Osteoarthritis-related knee pain: MRI-guided focused ultrasound ablation treatment - Christin A. Tiegs-Heiden; Zaiyang Long; Aiming Lu; Krzysztof R. Gorny; Gina K. Hesley (International Journal of Hyperthermia)
Objective: Osteoarthritis of the knee is a common cause of pain, functional disability, and reduced quality of life in the elderly. Despite its prevalence, there are limited currently available noninvasive treatment options. MRI-guided focused ultrasound (MRgFUS) is a noninvasive thermal ablation method which is used in a spectrum of musculoskeletal conditions. It is FDA approved for the treatment of painful bone metastases and osteoid osteoma and has been considered for the treatment of other painful conditions such as osteoarthritis. The purpose of this case report is to describe the use of MRgFUS for the treatment of osteoarthritic knee pain in an active 72-year-old male.Method: The patient suffered significant limitations due to lateral knee pain with jogging and walking down the stairs. MRgFUS ablation treatment was performed to the lateral knee, targeting the periosteum in the patients’ area of pain.Results: Following treatment, the patient experienced considerable reduction in his activity limiting symptoms with a duration of at least 6 months.Conclusions: It is important for radiologists to be aware of MRgFUS as an innovative ablation modality. Similar pain reduction was observed in two small series of MRgFUS treatment of knee pain from Japan. MRgFUS appears promising as a safe, noninvasive treatment option for temporary relief of knee pain. This may be particularly valuable for patients who are unwilling or unable to undergo total knee arthroplasty. Future study is needed to assess the efficacy and safety of this treatment in a larger population.